2018
DOI: 10.3390/ijms19061702
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Two Transcriptional Repressors and Chaperones Orchestrates Helicobacter pylori Heat-Shock Response

Abstract: The ability to gauge the surroundings and modulate gene expression accordingly is a crucial feature for the survival bacterial pathogens. In this respect, the heat-shock response, a universally conserved mechanism of protection, allows bacterial cells to adapt rapidly to hostile conditions and to survive during environmental stresses. The important and widespread human pathogen Helicobacter pylori enrolls a collection of highly conserved heat-shock proteins to preserve cellular proteins and to maintain their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(101 reference statements)
1
14
0
Order By: Relevance
“…In the human pathogen H. pylori , chaperones genes’ regulation by HspR and HrcA is built on an almost identical circuitry to the one here drawn for C. jejuni , where the regulon of HrcA appears to be entirely enclosed within the HspR regulon [ 36 ]. However, in H. pylori the two regulatory proteins bind to their operators in an independent manner and do not display any direct protein–protein interaction [ 13 , 37 ]. Indeed, in a previous work by our group, we assayed the DNA binding activities of HspR and HrcA under the same competitive conditions used in this work for the homologous regulators of C. jejuni .…”
Section: Discussionmentioning
confidence: 99%
“…In the human pathogen H. pylori , chaperones genes’ regulation by HspR and HrcA is built on an almost identical circuitry to the one here drawn for C. jejuni , where the regulon of HrcA appears to be entirely enclosed within the HspR regulon [ 36 ]. However, in H. pylori the two regulatory proteins bind to their operators in an independent manner and do not display any direct protein–protein interaction [ 13 , 37 ]. Indeed, in a previous work by our group, we assayed the DNA binding activities of HspR and HrcA under the same competitive conditions used in this work for the homologous regulators of C. jejuni .…”
Section: Discussionmentioning
confidence: 99%
“…This allows binding of RNA polymerase-σ 32 to the promoters of clp genes inducing the transcription of clpC and clpP . Following temperature-dependent autophosphorylation, McsB, assisted by McsA, targets CtsR to degradation by ClpCP protease (based on Krüger et al, 2001 ; Roncarati and Scarlato, 2017 ; Roncarati and Scarlato, 2018 ).…”
Section: Resistance Of L Monocytogenes To Stress mentioning
confidence: 99%
“…In response to a sudden temperature increase, bacterial cells promptly induce the expression of a group of proteins knows as heat-shock proteins (HSPs). The HSPs are crucial for cellular protection, survival, and adaptation to adverse environmental conditions [ 112 ]. Several studies have demonstrated the role of heat shock protein 1 (HSP1) in stabilizing the persistent infection mediated by CagA [ 113 , 114 ].…”
Section: Caga-dependent Mechanisms Of Pathogenicitymentioning
confidence: 99%